Sepsis in orthopaedic surgery: epidemiology, microbiology, treatment, consequences - Golubovska, Iveta; Solovjova, Elena; Vigante, Dace; Miscuks, Aleksejs; Jurkevics, Vitolds (Acta medica Lituanica, 2012)
Background. Musculoskeletal sepsis is a region of orthopaedic surgery focused on the diagnosis and treatment of infections involving the bones, joints, muscles, and skin. The objective of our study was to point out things that should be taken into account by physicians faced with probable musculoskeletal sepsis. Materials and methods. A retrospective study was carried out and included all of the orthopaedic patients with positive blood culture between January 1, 2009 and March 31, 2012 who were admitted to the Hospital of Traumatology and Orthopaedics. Results. In total, thirty five patients were hospitalized. Thirty one patients met the criteria for admission to the ICU. The median time spent in the ICU was 8 days with a range from 1 to 70. The source of infection was recognized in twenty five patients, it was not obvious for six patients. Moderate or severe septic shock developed in nineteen (61.3%) patients, twenty four (77.4%) required invasive monitoring, five PICCO monitoring, three of them required continuous haemodialysis. Overall mortality was 19.4% (six patients). 58.1% were artificially ventilated from 1 to 46 days. The main microbial culture was Staphylococcus aureus (45.2%), the second one was Clebsiella pneumoniae (12.9%), the third microbial cultures were Escherichia coli and Enterobacter cloacae (6.5%). More prevalent risk factors were diabetes mellitus, oncologic disease, ischemic heart disease and adipositas. Conclusions. Patients with a history of pain, swollen and tender joints, extremities or back with restriction of movement should be regarded as having septic inflammation until proven otherwise. We should always take into account orthopaedic sepsis if any other source is not obvious.
Keywords: musculoskeletal sepsis; orthopaedic surgery; diagnosis and treatment of infections